The effect of mental exercises accompanying performance on attention focus and shooting accuracy for young football players - شلال, م.د محمد محسن; Jawad, Prof. Dr. Ali Muhammad; Armout, Dr. Alaa Kazem (Sulaimani Journal for Humanities, 2026)
The study aimed to identify the effect of mental exercises accompanying performance in developing attention focus and shooting accuracy in football for young players. The researchers used the experimental method with the method of two equivalent groups. The research population was represented by the young players of Diwaniyah, whose number was (24) players for the training season 2024-2025 AD. They were divided into two groups, a control and an experimental group, each consisting of (12) players. Field tests were conducted for the two variables (attention focus and shooting accuracy). After that, mental exercises were applied through controlling and managing thoughts with performance. The most important conclusion of the researchers is that mental exercises are of great importance in the training process because skill performance requires focus and mental visualization, as well as the execution of the performance.